Innovative Accreditation Standards in Education and Training: The Italian Experience in Ethical Standards and the Impact on Business Organisation - Previtali, Pietro (Springer, 2016)
​The aim of this book is to examine how technical and institutional factors affect the responsiveness of public and private organisations to a change in accreditation standards, with specific reference to the vocational educational and training (VET) sector and ethical standards. In particular, the authors analyse the Italian experience regarding a new accreditation standard recently adopted in the Region of Lombardy. Although based on a national experience, this innovative approach to accreditation systems in the educational sector provides a more general framework of analysis of how ethics and compliance can be applied in business organisation worldwide.